Fabrication and characterization of silicon-on-insulator using low temperature wafer bonding - Yu, Weibo (2008)
In present study, two low temperature wafer bonding methods, namely the medium vacuum wafer bonding (MVWB) and plasma activated wafer bonding (PAWB), are studied.